Crescimento inicial de plantas de Camu-camu sob fertirrigação com nitrogênio e potássio em condições de terra firme - Rodriguez, Carlos Abanto (2014)
One of the trends of the present world is the orientation to the consumption of natural products with a high nutritive and vitamin value. The camu-camu is a fruit-bearing tree native to the Amazon rainforest, which calls the attention for its high vitamin C content (up to 6,116 mg/100 g of pulp). This species is in domestication process; for this reason, technical information about the agronomical management on firm earth in the early years of cultivation is not available. So, it was aimed to determine the effect of both nitrogen and potassium applied for nine months via fertigation on the early growth of camu-camu plants irrigated under firm earth conditions (January-September, 2013). For such a purpose, two experiments were carried out: the former consisted in the application of five doses of nitrogen: 0; 40; 80; 120 and 160 kg ha-1; and in the latter, five doses of potassium: 0, 40, 80, 120 and 160 kg ha-1 were tested. The designs utilized were in randomized blocks in split plot scheme in time for the variables: height (cm), stem diameter (mm) evaluated every 30 days; number and total length of twigs evaluated every 90 days (cm) and simple randomized blocks for the a chlorophyll content, dry mass (g) of leaves, of the twigs, of the roots, total dry mass (g), Dickson quality index (IQD), content and accumulation of macro and micronutrients evaluated at the end of the experiments. Based upon the results, it was found that nitrogen and potassium fertilization applied via fertigation brought about improved quality of the camu-camu plants at the approximate dose of 128 kg ha-1 of N and 160 kg ha-1 of K. Nitrogen fertilization increased the contents of N, K and Ca and reduced the contents of B and Mn, the potassium fertilization raised the contents of N, K and S and reduced the contents of Ca, Mg, B and Mn in the camu-camu leaves. Considering the parts of the plant, the greatest accumulation of nutrients was found in the shoot (twigs and leaves) for N, P, K, Ca, Mg, S, B and Mn and for the roots was Fe, Cu and Zn as a result of the growing doses of N e K.